Relevance of Polymorphism of Glutathione S-Transferase Genes (GSTM1 and GSTT1) in Diabetic Retinopathy and Diabetic Nephropathy - Vaishali S. Pawar; Kailas D. Datkhile; Ajit V. Sontakke; Satyajeet K. Pawar; Prajakta S. Patil (Indian Journal of Endocrinology and Metabolism)
Introduction: The causative factors of diabetic retinopathy and nephropathy are genetic as well as environmental. The Glutathione S-transferase gene family is involved in redox balance to reduce oxidative stress, which is an important factor associated with these major diabetic complications. The objective of this study was to investigate the association between the polymorphism of glutathione S-transferase genes (GSTM1 and GSTT1) and type 2 diabetes mellitus (T2DM) patients with diabetic retinopathy (DR) and diabetic nephropathy (DN). Methods: In this cross-sectional study, GSTM1 and GST1 gene polymorphisms were studied in T2DM patients with three groups of 125 cases each: the 1st group DM without DN and DR, the 2nd group with DR, and the 3rd group with DN from December 2019 to January 2023. Polymerase chain reaction (PCR) was performed on DNA. GSTM1 and GSTT1 genotyping was conducted using gel electrophoresis. Statistical analysis was performed using SPSS software. Results: Compared to the DM group, in the DR group, the GSTT1 null and GSTM1 null genotypes were more prevalent and showed 2.68-folds (OR = 2.68; 95% CI = 1.60–4.48; P < 0.001) and 2.5-folds (OR = 2.50; 95% CI = 1.50–4.18; P < 0.001) increased risk of developing DR respectively. In the DN group, the GSTM1 null genotype was more prevalent, with a 1.97-fold increased risk of developing DR (OR = 1.97, 95% CI = 1.19–3.26; P = 0.008) when compared to the DM group. However, no significant difference was found in the GSTT1 null genotype between the DN and DM groups. Conclusion: The significant association between null genotypes of both GSTT1 and GSTM1 with DR and only the GSTM1 null genotype with DN suggests their roles as risk factors.